Anti-inflammatory mechanism of total flavonoids from Polygala fallax Hemsl. based on network pharmacology, molecular docking, and experimental validation - Liao, Chunhong; Su, Hua; Li, Fengzhen; Wang, Chenglong; Yang, Sufang; Qin, Zujie; Li, Ning (Frontiers in Immunology, 2025)
ObjectiveTo explored the anti-inflammatory mechanisms of total flavonoids of Polygala fallax Hemsl. (PFHF) using network pharmacology, molecular docking, and cellular experiments.MethodsKey components, targets, and pathways of PFHF were identified via literature and network pharmacology, with molecular docking and dynamics simulations validating binding to therapeutic targets. RAW264.7 cells were treated with lipopolysaccharide (LPS) to establish inflammation, and groups included blank controls, LPS-induced models, prednisolone acetate, and low/high-dose PFHF. Cytokine levels (IL-6, TNF-α, IL-1β) were measured by ELISA, while immunofluorescence assessed protein expression post-PFHF treatment.ResultsSix major active components were identified, alongside 44 active components, 1,178 inflammatory genes, and 18 target genes. Core targets included IL-6, TNF, IL1B, INS, and CASP3. Gene Ontology (GO) analysis linked these targets to protein localization, membrane rafts, and receptor activity. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways highlighted IL-17, TNF, and NOD-like receptor signaling. Molecular docking confirmed rutin’s strong binding to IL-6, TNF, IL-1β, INS, and CASP3. HPLC quantified rutin at 0.09 mg/mL. PFHF inhibited RAW264.7 proliferation with IC50 values of 206.32 µg/mL (24h) and 102.39 µg/mL (48h). High-dose PFHF reduced IL-6, TNF-α, and IL-1β (P<0.05) versus the model group. Immunofluorescence revealed elevated INS (P<0.05) and reduced CASP3 (P<0.01), iNOS, and Cox-2 (P<0.0001) in treated cells.ConclusionPFHF exerts anti-inflammatory effects via IL-17 and TNF pathways, targeting IL-6, TNF-α, INS, IL-1β, and CASP3, mediated by rutin and other components.